SECONDARY BIOACTIVE METABOLITE GENE CLUSTERS IDENTIFICATION OF ANTICANDIDA-PRODUCING Streptomyces Sp. GMR22 ISOLATED FROM WANAGAMA FOREST AS REVEALED BY GENOME MINING APPROACH - Camelia Herdini; Sofia Mubarika; Bambang Hariwiyanto; Nastiti Wijayanti; Akira Hosoyama; Atsushi Yamazoe; Hideaki Nojiri; Jaka Widada (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
Streptomyces are a group of Gram-positive bacteria belonging to the Actinobacteria class, which are among the most important bacteria for producing secondary bioactive metabolites such as antibiotics, chemotherapeutics, insecticides and other high-value chemicals. Genome mining of gene clusters that encode the biosynthetic pathways for these metabolites has become a key methodology for novel compound discovery. Recently, we have isolated the Streptomyces sp. GMR22 from Cajuput rhizospheric soil at Wanagama Forest, Indonesia. GMR22 produced secondary metabolite that inhibited Candida albicans with IC50 of 62,5 μg/mL. The objective of this work was to reveal the novel secondary metabolites from GMR22 by genome mining approach. The antiSMASH 3.0 was used to predict gene clusters that encode the biosynthetic pathways of secondary metabolites in the genome of GMR22, and their core chemical structures. The pylogenomic analysis showed that GMR22 was closely related to Streptomyces bingchenggensis BCW1, as well as to the large genome size (9.5-12.7Mbp) groups of Streptomyces. AntiSMASH 3.0 analysis revealed that the genome of Streptomyces sp. GMR22 harbored at least 63 gene clusters that encode the biosynthetic pathways of secondary metabolites. It was the highest number of gene clusters had been observed among the members of Streptomyces groups, with PKS was predicted as the major groups of the identified gene cluster products. The results suggested that GMR22 could be a strong potential candidate of secondary bioactive metabolites source.